Relationship Between Post-Fire Vegetation Recovery and Soil Temperature in the Mediterranean Forest - Giulia Calderisi; Enrico Salaris; Donatella Cogoni; Ivo Rossetti; Filippo Murtas; Giuseppe Fenu (Fire)
In Mediterranean regions, fires are a key ecological factor, altering soil properties, biodiversity, and landscape dynamics. Post-fire recovery varies based on vegetation type, fire severity, and climate conditions. However, the specific relationship between post-fire vegetation recovery and soil temperature regimes remains poorly investigated. This study investigates this relationship in an area severely affected by a megafire. Three plots (unburned, low-severity fire, and high-severity fire) were monitored for species richness, vegetation cover and height, and soil temperature, with data from 2021 to 2024 analyzed. Vegetation surveys revealed that fire severity influenced species richness and vegetation cover and height. Particularly, burned areas showed a higher proliferation of pioneer and herbaceous species three years post-fire. Moreover, after the same period, burned areas showed consistently higher soil temperatures than the unburned ones, reflecting altered microclimatic conditions. This could be because the presence of more pioneer and herbaceous species is insufficient to mitigate the air temperatures. Our results show the impact of fires on soil and vegetation, highlighting the critical role of vegetation in modeling soil temperature. However, long-term monitoring is necessary to assess the real effect of vegetation type on soil temperature.